Cost analysis showed that feeding preterm infants with donor human milk was significantly more expensive than mother's milk or formula. (22nd November 2019) - Fengler, Josefine; Heckmann, Matthias; Lange, Anja; Kramer, Axel; Flessa, Steffen
Abstract: Aim: This study analysed the comparative cost of feeding donor human milk to preterm infants compared to mother's own milk and formula. Methods: A document and process analysis and a time measurement study were carried out at the milk bank of the Level 1 Perinatal Center of the University Hospital of Greifswald, Germany, from April to June 2017. The cost analysis data were provided by the University's financial department. Results: The total cost per year was €92 085.02 for 300 litres of donor human milk: 27% of this was material costs, 51% was personnel costs, and 22% was other overheads. The average cost per litre was €306.95, and staff time was 492 minutes per litre. The total marginal cost for each additional litre of donor human milk, formula or unpasteurised mother´s milk was €82.88, €10.28 and €38.42, respectively. Pasteurising a litre of donor milk cost €3.51. Conclusion: Providing preterm infants with donor milk was much more expensive than using formula or mother's own milk, but the cost of pasteurisation was minimal.